2012
DOI: 10.1155/2012/123725
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic User Portraits

Abstract: User modeling and profiling has been used to evaluate systems and predict user behaviors for a considerable time. Models and profiles are generally constructed based on studies of users’ behavior patterns, cognitive characteristics, or demographic data and provide an efficient way to present users’ preferences and interests. However, such modeling focuses on users’ interactions with a system and cannot support complicated social interaction, which is the emerging focus of serious games, educational hypermedia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Teixeira et al, 2012), it is noteworthy that the analyses reported in the reviewed papers typically concern experiences that are common or typical rather than individual or subjective (e.g. Baranova et al, 2011;Clatworthy, 2010;Huang et al, 2012;Johns and Clark, 1993;Mangiaracina et al, 2009;Rasila et al, 2009) based on data gathered at the level of individual customers and some, such as Crosier and Handford (2012), also report on example qualitative data from individual customers.…”
Section: Customer Journeys To Investigate and Communicate Common Expementioning
confidence: 99%
See 4 more Smart Citations
“…Teixeira et al, 2012), it is noteworthy that the analyses reported in the reviewed papers typically concern experiences that are common or typical rather than individual or subjective (e.g. Baranova et al, 2011;Clatworthy, 2010;Huang et al, 2012;Johns and Clark, 1993;Mangiaracina et al, 2009;Rasila et al, 2009) based on data gathered at the level of individual customers and some, such as Crosier and Handford (2012), also report on example qualitative data from individual customers.…”
Section: Customer Journeys To Investigate and Communicate Common Expementioning
confidence: 99%
“…The journeys are typically visualized as processes spanning a number of steps, stages, touchpoints, or activities; as a horizontal line or row (11 papers, e.g. Bridge, 2012;Huang et al, 2012;Peterson et al, 2010) or a vertical line or column ( Johns and Clark, 1993;Rasila et al, 2009;Whittle and Foster, 1991). The visualizations were found to be augmented with diverse types of information such as customer emotions (e.g.…”
Section: Customer Journeysmentioning
confidence: 99%
See 3 more Smart Citations